2004
DOI: 10.1016/j.jacc.2003.11.032
|View full text |Cite
|
Sign up to set email alerts
|

The Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) study

Abstract: Rate control in AF is possible in the majority of patients with AF. Beta-blockers were the most effective drugs. To achieve the goal of adequate rate control in all patients, frequent medication changes and drug combinations were needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(72 citation statements)
references
References 37 publications
2
68
0
2
Order By: Relevance
“…In accordance to previous studies, left atrial maximum common diameter is higher and left ventricular EF is lower in patients with AF recurrence (group B) than in those with SR predominance (group A) [33][34][35]. However, these variables could not stratify patients in one of the two groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance to previous studies, left atrial maximum common diameter is higher and left ventricular EF is lower in patients with AF recurrence (group B) than in those with SR predominance (group A) [33][34][35]. However, these variables could not stratify patients in one of the two groups.…”
Section: Discussionsupporting
confidence: 89%
“…However, we overcame this limitation by dividing patients according their arrhythmic burden (groups A and B). Since more and long-lasting AF episodes may be more deleterious than less and very short periods of arrhythmia (in terms of risk due to the adverse results of AF), this division has been suggested as being more useful in clinical practice for the patients' clinical stratification and treatment [14,34].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of metoprolol, propranolol and esmolol reduces ventricular response in patients with atrial fibrillation (AF) within 5 minutes of administration [45], and both intravenous and oral regimens attain resting and exercise rate control, variably defined, in 68–75% of patients [28], [46]–[48]. Rate lowering efficacy varies with acuity and cardiac function and is enhanced with digoxin [46], [47].…”
Section: Recommendations and Reasoningmentioning
confidence: 99%
“…The adequate control of ventricular rate constitutes an essential aspect of AFib management [611]. However, no consensus on how to define proper control exists.…”
Section: Discussionmentioning
confidence: 99%
“…This is why the optimal control of ventricular rate during AFib has gained considerable clinical importance. Recent publications of randomized trials have shown that strategies of rate control and sinus rhythm maintenance are equivalent, as measured by various end points [711]. Unfortunately, the definition of adequate rate control is somewhat arbitrary.…”
Section: Introductionmentioning
confidence: 99%